Adherence to 24-h Movement Guidelines and Depressive Status During the Coronavirus Disease Outbreak: A Cross-Sectional Japanese Survey - Takahisa Ohta; Takahisa Ohta; Madoka Ogawa; Naoki Kikuchi; Hiroyuki Sasai; Takanobu Okamoto (International Journal of Public Health, 2023)
Objectives: The coronavirus disease 2019 (COVID-19) pandemic has affected people’s physical activity, sedentary behavior, and sleep. This study aimed to clarify the association between combining these factors, integrated as adherence to 24-h movement guidelines, and depressive status during the COVID-19 pandemic.Methods: At the end of October 2020, we sent self-administered questionnaires to 1,711 adults aged ≥18. We assessed physical activity, sedentary behavior, sleep duration, adherence to 24-h movement guidelines, depressive status, and confounding factors.Results: Of the 640 valid responses, 90 (14.1%) reported a depressive status. Multivariable odds ratios (95% confidence interval) of depressive status were 0.22 (0.07, 0.71) for all three recommendations of the 24-h movement guidelines and those who met none of the recommendations as reference. The number of guidelines met was associated with depressive status in a dose-response fashion.Conclusion: Meeting the 24-h movement guidelines was associated with a lower prevalence of depressive status during the COVID-19 pandemic. Adults should adhere to these guidelines to maintain their mental health during future quarantine life.